Factors Affecting Quality of Life in Patients with Coronary Artery Disease - Teguh Santoso; Untung Sujianto; Dwi Susilawati (IJNP (Indonesian Journal of Nursing Practices), 2017)
Background: Coronary artery disease caused disturb of physical, psychological, and social aspects on quality of life. The aims in this study was to examine effecting factors of quality of life (QoL).Methods: In this used the analytic correlation with cross-sectional design. One hundred and three subjects paticipated with purposive sampling (88 male and 23 female). QoL quesioner (SF-36) were used to collect the data. The data were analyzed by multivariate regression.Results: One hundred and three patientss (80 males and 23 female) were enroll on this study. In this study indicates that independent variables were not associated with quality of life (p value 0.05). The greater quality of life found in patients graduated from university (62,2%) and had much income (51.9%). Other variables like male (57.5%), patients between 48-57 years of ages (68.2%), married patients with coronary artery disease (62.0%), the retired or unemplayee (78.9%), patients with hypertention (57.8%), never taking alcohol (60.8%), never smoking (50%) and never doing exercise (66%) had lower quality of life score.Conclusion: There were no statistically significant factors affecting quality of life in patients with CAD. The more respondents needed to know the factors affecting quality of life